Prisoners of Culture : Representing the Vietnam P.O.W - Gruner, Elliott (Book collections on Project MUSE., 1993)
Can we separate our image of the Vietnam War from our image of the American POW? And can we separate our image of the United States from myths surrounding that war and those hostages? In this daring and controversial new book, Elliott Gruner examines how POW mythology emerged from national legends going back to the colonial period, how the media and the government have portrayed prisoners of war in the past, and how the Vietnam POW in particular, became a prisoner of agendas set by others for their own purposes. POWs have been featured in literature, advertising, films, television, documentary news, and on audio cassettes. They have been feted, awarded medals, and paraded before us. We can find depictions of them on bracelets, flags, and the covers of national magazines. We have competing images of POWs like Sylvester Stallone's rampaging Rambo, James Stockdale, the hero who became a vice-presidential candidate, Robert DeNiro in a barbed-wire cage in the Deer Hunter, and Jeffrey Zaun looking battered on magazine covers during the Gulf War. Prisoners of Culture is about how we make sense of these pervasive images. In it, Gruner illuminates the assumptions behind all of these texts. He sorts out what is real and what is myth. He looks at the ways POWs have been used to portray the strength of America, the might of capitalism, the power of whiteness and of masculinity. He forces us to question what we would like to believe about ourselves and challenges us to discard the myths before they do us even greater harm.